Efficiency of Gene-Activated Osteoplastic Material with Plasmid DNA Containing VEGF Gene for Bone Defects Healing - Deev, Roman V.; Bozo, Ilya Ya.; Drobyshev, Aleksey Yu.; Isaev, Artur A. (Problems of Cryobiology and Cryomedicine, 2013)
N/A Probl Cryobiol Cryomed 2013; 23(4):355–358.